Analisis e-book fisika SMA kelas X semester ganjil didasarkan pada integrasi literasi informasi - Hasbi Aziz; Yumelda Marzuki; Festiyed Festiyed (PILLAR OF PHYSICS EDUCATION, 2019)
Entering the 21st century one component of basic literacy is information literacy. At this time with various facilities and availability of facilities, and various demands that require everyone to be capable and sophisticated with information. The global era with many phenomena of information requires the ability to be able to access the information wisely. Literacy is more than just reading and writing, but includes thinking skills using knowledge sources in printed, visual, digital and auditory books. In this 21st century, this ability is called information of literacy. One of the supporting facilities that support the information in learning is teaching materials. However, teaching materials that are often used by students are printed books. In this digital era, it is very easy for us to access and use the process of non-printed teaching materials (e-books). It can also be used as textbooks that support students to increase information literacy. Therefore non-printed teaching materials (e-books) should contain information literacy to support learning. The purpose of this research is to obtain information about the scope of information literacy which are includes media literacy, technology literacy and visual literacy in e-books in circulation. This research uses descriptive research method. The research population was all material in the odd semester High School Physics e-books analyzed. The population in this research was taken all the material to be sampled. The instrument used as an observation sheet is an observation sheet containing information literacy indicators. From the five e-books analyzed based on aspect of information literacy, was obtained the results of the average suitability obtained for each e-book that is in e-book 1 has a value of 46% with a less good category.  In e-book 2 has a value of 71% with a good category. In e-book 3, it has a value of 54% with a less good category.  In e-book 4, it has a value of 48% with a less good category.  Finally in e-book 5 it has a value of 61 with a less good category.